Synthesis and biological evaluation of chalcone derivatives containing aminoguanidine or acylhydrazone moieties. Issue 24 (15th December 2016) - Wei, Zhi-Yu; Chi, Ke-Qiang; Yu, Zhan-Kui; Liu, Hong-Yan; Sun, Liang-Peng; Zheng, Chang-Ji; Piao, Hu-Ri
Graphical abstract: Three novel series of chalcone derivatives containing aminoguanidine or acylhydrazone moieties were designed, synthesized, characterized and evaluated for their antibacterial activity, antifungal activity and anti-inflammatory activity. Abstract: Three novel series of chalcone derivatives containing an aminoguanidine or acylhydrazone moiety were designed, synthesized and evaluated in terms of their antibacterial, antifungal and anti-inflammatory activities. Most of the synthesized compounds showed potent inhibitory activity towards various bacteria and one fungus with minimum inhibitory concentrations (MICs) ranging from 1 to 8 μg/mL. Compared with our previously reported chalcone derivatives (MICs >64 μg/mL), these compounds exhibited improved antibacterial activities (MICs = 2 μg/mL) against Gram-negative bacterial strains ( Escherichia coli 1924 and 1356). Compounds4f and4h were found to be the most potent with an MIC value of 1 μg/mL against the Gram-negative bacterial strains Salmonella typhimurium 1926 and the fungus Candida albicans 7535. In addition, compound4f displayed the most potent anti-inflammatory activity of all of the compounds prepared in the current study with 92.45% inhibition after intraperitoneal administration, making it more potent than the reference drugs indomethacin and ibuprofen. The cytotoxic activity of the compound4f was assessed in HeLa, Hep3B and L02 cells.